A male Covid-19 convalescent plasma donor with long existence of SARS-Cov-2 antibodies: a case report - Teguh Triyono; Usi Sukorini; Andri Christianalusi; Sri Mulatsih; Hans Vrielink (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2023)
Covid-19 Convalescent Plasma (CCP) was one of alternative therapy for Covid-19 patients. The use of convalescent plasma as an adjunct therapy must consider its efficacy, benefits, and risk, both for the patient and the donor. Convalescent Plasma was produced from purified human plasma. Convalescent Plasma was a passive immunity which provide active antibodies. CCP give immunity to the patient through the transfusion of a survivor’s antibodies. We were reporting a case of male CCP donor with long existence of SARS-Cov-2. This donor performed up to 16 donations, which was an unusual case in CCP donor. The SARS-CoV-2 antibody titer was analyzed using Elecsys® Anti-SARS-CoV-2 (Roche Diagnostics). The SARS-CoV-2 antibody showed high level of total SARS-CoV-2 antibodies, with the Cut off Indexes (COI) anti SARS-Cov-2 antibody were still quite high (132 U/mL). The highest donor antibody COI (204.6 U/mL) was seen in 11th donation at 6 months after recovery, while the lowest antibody COI (130.8 U/mL) was in 15th donation at 7 months after recovering. Evaluation of donor health status were performed after the 16th donation and analyzed as well. In conclusion, 16 CCP donations of 600 mL resulting in 48 units of 200 mL plasma in 8 months was safe for the donor, with the SARS-Cov-2 antibody titer remained high in the whole period.